2011
DOI: 10.1007/s10902-010-9246-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and Subjective Well-Being: Affectivity Plays a Secondary Role in the Relationship Between Optimism and Global Life Satisfaction in the Middle-Aged Women. Longitudinal and Cross-Cultural Findings

Abstract: The focus of the present study lies on optimism and its relationships to the components of subjective well-being, i.e. global life satisfaction, positive affect and negative affect. We investigated the direct and indirect (via affectivity) effects of optimism on global life satisfaction in the Swedish middleaged women at two time points (age 43 and 49), and in the Lithuanian middle-aged women. For this purpose, structural equation modelling was used and the fit indices were compared between two cognitive-affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 42 publications
(59 reference statements)
7
48
0
3
Order By: Relevance
“…This study’s findings indicated that self-efficacy and optimism explained part of the variability of the participants’ psychological and subjective well-being and that empathy explained an incremental variability. Self-efficacy and optimism jointly explained a moderate-to-large portion of the variability in positive psychological functioning, in line with previous evidence of such a positive role in other populations [ 27 , 28 , 41 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 88%
“…This study’s findings indicated that self-efficacy and optimism explained part of the variability of the participants’ psychological and subjective well-being and that empathy explained an incremental variability. Self-efficacy and optimism jointly explained a moderate-to-large portion of the variability in positive psychological functioning, in line with previous evidence of such a positive role in other populations [ 27 , 28 , 41 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 88%
“…Optimism is also associated with increased psychological well-being, fewer perceived stressors, a lower tendency to be depressed and problem-solving coping. Furthermore, optimism has been associated with higher scores in life satisfaction, positive effects, selfesteem, self-acceptance, positive relations with others, autonomy, environment mastery and personal growth (Bailey, Eng, Frisch, & Snyder, 2007;Chang, 2009;Daukantaite & Zukauskiene, 2012;Hart, Vella, & Mohr, 2008;Vacek, Coyle, & Vera, 2010). Optimism is also associated with the ability to find meaning after negative life events (Nolen-Hoecksema, 2000), and is not inevitably altered by changes in disease status .…”
Section: Discussionmentioning
confidence: 99%
“…Human capital in terms of education and language skills, the latter being of special importance for immigrant and ethnic minorities, are also related to life satisfaction (Amit, ). Other factors which can positively affect life satisfaction are health conditions (Bartram, ; Knight & Gunatilaka, ) and optimism (Daukantait≐ & Zukauskiene, ). Mood may determine more than seventy percent of how much life satisfaction an individual reports (Seligman, ).…”
Section: Introductionmentioning
confidence: 99%